Análisis de la erupción del incisivo lateral superior en comparación a los estándares establecidos de la cronología de la erupción dental en estudiantes de la Unidad Educativa Carlos Cisneros, Riobamba - Pino Vela, Guido Oswaldo (2017)
TRADUCCION AL INGLES TITLE: The development of dental structures is the result of a complex process of reciprocal and sequential interactions between epithelial and mesenchymal cells. The dental organogenesis is under strict genetic control, involving growth factors, transcription factors, signaling molecule and proteins that determine the position, number and shape of different teeth. Alterations in this process could explain the appearance of dental anomalies such as agenesis, delays in the eruption and alterations in size, shape and position. The objective of this study is to observe the eruption of the lateral superior incisor in comparison to the established standards of the chronology of the dental eruption in students of the Carlos Cisneros Educational Unit, Riobamba. In this investigation the cases of delay of the upper lateral incisor flare accounted for 10%. The patterns of delay varied between genders, with the male being the most affected at a ratio of 2: 1, which agrees with studies in which a higher frequency of delay is observed in the male sex. The dental eruption is determined by several factors such as: sex, age, nutritional status, race, heredity, skeletal development, the history of premature extractions of primary teeth, the size of teeth with respect to the the jaws, the genetic factors, some factors of the intrauterine and postnatal development, as well as the elements of the environment and the socioeconomic level. As a result, it was possible to know the Nolla stage of the patients who, in the intraoral examination, did not present macroscopic evidence and after the radiographic examination was corroborated, that the nutritional factor that is evidenced in the weight and height, influences in a significant way in the eruption of the dental pieces, all this based on the application of percentiles of the WHO that correspond to weight and height according to the chronological age that for the effect is of 8 and 9 years.